Improving village governance in contemporary China - He, Xuefeng, 1968- (Social sciences of practice, 2021)
"Based on an in-depth investigation of different regions of China's vast countryside, Improving Village Governance in Contemporary China vividly describes rural governance mechanisms against the background of China's rapid urbanization. China's rural areas vary greatly from region to region with respect to the pace and mode of change. Rural governance in China is decided by how the state transfers resources to villages, and by the linkage between the transfer style and the specific situation of each village. Only when grassroots governance is based on rural democracy (with peasants as the core) can villages become more harmonious"--